Risk of Death After Paclitaxel Exposure During Femoropopliteal Artery Angioplasty – Narrative Review - Ribeiro, T (2021)
Paclitaxel molecule has been on the market since 1991 and is indicated for the treatment of multiple neoplasms. Since 2012 has been used in endovascular devices for the treatment of peripheral artery disease and have become a mainstay in the treatment of symptomatic femoro-popliteal lesions, in particular for preventing arterial restenosis. They have a proven benefit in patency and freedom-from re-intervention up to 5 years. A recent meta-analysis of RCT showed an increased late-mortality rate, however, real-life cohorts analyses presents contradictory results. RCT meta-analysis is comprised mainly by claudicants, and CLTI patients are underrepresented. Further studies are needed to clarify this matter, in particular with a higher percentage of CLTI presentation. For now, patients should be advised about risks and benefits of paclitaxel exposure and a shared decision-making process should be followed.